Long-term weight changes and risk of rheumatoid arthritis among women in a prospective cohort: a marginal structural model approach. (10th July 2021) - Marchand, Nathalie E; Sparks, Jeffrey A; Malspeis, Susan; Yoshida, Kazuki; Prisco, Lauren; Zhang, Xuehong; Costenbader, Karen; Hu, Frank; Karlson, Elizabeth W; Lu, Bing
Abstract: Objective: To examine the association of long-term weight change with RA risk in a large prospective cohort study. Methods: The Nurses' Health Study II started in 1989 (baseline); after exclusions, we studied 108 505 women 25–42 years old without RA. Incident RA was reported by participants and confirmed by medical record review. Body weight was reported biennially through 2015. We investigated two time-varying exposures: weight changes from baseline and from age 18; change was divided into five categories. We used a marginal structural model approach to account for time-varying weight change and covariates. Results: Over 2 583 266 person-years, with a median follow-up time of 25.3 years, 541 women developed RA. Compared with women with stable weight from baseline, weight change was significantly associated with increased RA risk [weight gain 2–<10 kg: RR = 1.98 (95% CI 1.38, 2.85); 10–<20 kg: RR = 3.28 (95% CI 2.20, 4.89); ≥20 kg: RR = 3.81 (95% CI 2.39, 6.07); and weight loss >2 kg: RR = 2.05 (95% CI 1.28, 3.28)]. Weight gain of 10 kg or more from age 18 compared with stable weight was also associated with increased RA risk [10–< 20 kg: RR = 2.12 (95% CI 1.37, 3.27), ≥20 kg: RR = 2.31 (95% CI 1.50, 3.56)]. Consistent findings were observed for seropositive and seronegative RA. Conclusion: Long-term weight gain was strongly associated with increased RA risk in women, with weight gain of ≥20 kg associated with more than a three-fold increased RA risk. Maintenance of healthy weight may be a strategy to prevent or delay RA.